Screening of north-east Mexico medicinal plants with activities against herpes simplex virus and human cancer cell line - Silva Mares, David Arturo; Rivas Galindo, Verónica Mayela; Salazar Aranda, Ricardo; Pérez López, Luis Alejandro; Waksman de Torres, Noemí; Pérez Meseguer, Jonathan; Torres López, Ernesto (Taylor & Francis Health Sciences, 2019)
The plants examined in this study have previous biological activity reports indicating the possibility of found activity against herpes and cancer cell. The aim of this contribution was to carry out a screening of Juglans mollis (Juglandaceae), Persea americana (Lauraceae), Hamelia patens (Rubiaceae), Salvia texana (Lamiaceae), Salvia ballotaeflora (Lamiaceae), Ceanothus coeruleus (Rhamnaceae), Chrysactinia mexicana (Asteraceae) y Clematis drummondii (Ranunculaceae), against HeLa cells, VHS-1 and VHS-2. The method MTT was used to determine the 50% cytotoxic concentration (CC50), in Vero and HeLa cell lines. To determine the 50% inhibitory concentration (IC50) against herpes, the plaque reduction method was used. Results showed that none of the plants exhibited activity against HeLa cells. About antiherpetic activity, J. mollis and S. ballotaeflora extracts present antiherpetic activity in terms of their SI, increasingly interest for further studies on the isolation of compounds with antiherpetic activity and about the mechanisms of action that produce this activity.